Experiences of the Redesigning Daily Occupation programme – a qualitative study among persons with neurological diseases - Carina Sandström; Elin Mårtensson; Therese Hellman (Scandinavian Journal of Occupational Therapy)
Background The Redesigning Daily Occupations (ReDO) is a programme targeting persons who need to restructure activities and routines to achieve a healthier balance in everyday life. Issues that often is needed for persons with neurological diseases.Aims/Objectives To describe how persons with neurological disease experienced the ReDo-programme and to investigate how their occupational patterns and fatigue changed during the programme.Material and Methods A mixed method study with a convergent parallel design including ten participants. Questionnaires and individual semi-structured interviews have been used and data analysed by descriptive statistics and thematic analysis.Results The findings indicated an increased participation in everyday life after the intervention. Furthermore, the main theme showed that the intervention enabled reflections and new insight. Sub-themes included: feeling pressured to perform, being part of a group and changing occupational pattern.Conclusions Participants valued being a group; however, they experienced the intensity as being too high. The content of the intervention enabled reflections and new insights regarding their occupational pattern, which was experienced as a starting point towards behavioural changes and re-prioritisation of occupations in everyday life.Significance A modified version with lower intensity and careful goal setting might be valuable for persons with neurological diseases.